ANALISIS PENGARUH WORK-LIFE BALANCE TERHADAP EMPLOYEE ENGAGEMENT DENGAN JOB SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi Pada PT Barata Indonesia) - Alfiya Jannata; Mirwan Surya Perdhana (Diponegoro Journal of Management, 2022)
This study aims to determine the relationship between work-life balance, job satisfaction, and employee engagement of PT Barata Indonesia’s employee. This research is in the form of quantitative research using a questionnaire as a method of data collection. The sample used in this study is 109 organic employees of PT Barata Indonesia and the method is probability sampling with simple random sampling technique. The data analyzed using SPSS AMOS 24 (Confirmatory Factor Analysis and SEM assumptions which is normality assessment, outliers assessment, singularity and multicollinearity assessment, evaluation of residual covariances, reliability and variance extract, also hypothesis testing). The result of this study indicate that work-life balance have a positive and significant effect on job satisfaction and employee engagement. Whereas job satiscation also have a positive and significant effect on employee engagement.